Similarity Solution to Cylindrically Converging Symmetric Magneto Hydrodynamic (MHD) Shock in a Non-Ideal Gas with Total Energy - Revathi, Ravilisetty; Ramu, Addepalli (Discontinuity, Nonlinearity, and Complexity, 2026)
A similarity solution for cylindrically converging shock waves of symmetric flow in MHD propagating into a medium, plasma governed by the equation of state (EOS) of Mie-Gruneisen type, is calculated. The governing equations of flow with total energy and constant specific heats are considered in the Eulerian form. These equations are reduced to a system of differential equations of Poincare type using similarity transformations. The transformed system is then reduced to a finite difference system of equations and solved numerically using MATLAB. In the present work, different non-ideal EOS of Mie-Gruneisen type are considered with suitable material constants. Similarity exponent α, which varies with the measure of shock strength, β for the considered EOS are evaluated. It is observed that the measure of shock strength β affects the shock front. Further, the effect of non-idealness parameters, magnetic field strength on the flow variables are presented.